Evaluation And Monitoring as An Effort to Improve the Quality of Education - Rosmalina, Rosmalina; Elfrianto, Elfrianto (Indonesian Journal Education, 2024)
The research aims to find out a comprehensive picture regarding evaluation and monitoring as an effort to improve the quality of education. The research focuses on qualitative methods with a literature review approach. Literature reviews focus on developing pre-existing concepts and theories by utilizing information available from various journals, books, government regulations and other relevant references. Based on the results of the literature review, it can be concluded that evaluation and monitoring are very important in efforts to improve the quality of education, where by evaluating and monitoring the education system can be improved through various new policies that have clear orientation and objectives so that these policies can be implemented well. Apart from that, evaluation and monitoring can provide an overview of the advantages and disadvantages of policies that have been applied previously, so it is hoped that the education system and quality in Indonesia will improve